Psychosocial impact of hidradenitis suppurativa: a practical guide for clinicians. (19th May 2022) - Weigelt, Maximillian A.; Milrad, Sara F.; Kirby, Joslyn R. S.; Lev-Tov, Hadar
Abstract: Introduction: Hidradenitis suppurativa (HS) is a debilitating skin disease with significant and often underappreciated effects on quality of life; available treatments fail to achieve consistent rates of remission. Targeting the psychosocial impact of HS has great potential to improve care for these patients. Although the literature on this topic is broad, there is a lack of specific tools that guide clinicians in this domain. Methods: The authors surveyed the literature to find the aspects of psychosocial functioning that most significantly impact Health-Related Quality of Life (HRQOL) for HS patients, and which may be assessed in a simple and efficient manner. Results and discussion: Depression and anxiety, sexuality and body image, and financial strain were identified as the most significant drivers of poor HRQOL with the greatest potential to be screened for and addressed succinctly and effectively. A practical psychosocial management guide for clinicians is presented. The guide includes a list of preexisting validated screening questions, clear guidelines for interpretation, and a suggested management algorithm all geared toward a 'real-life' medical practice. Conclusion: Such an approach holds a great potential for improving the care of patients with HS. Validation of this approach via controlled trials is a logical next step.